Electrochemical Corrosion of Titanium and Titanium Alloys Anodized in H2SO4 and H3PO4 Solutions - Jáquez Muñoz, Jesús Manuel; Gaona Tiburcio, Citlalli; Chacón Nava, José G.; Cabral Miramontes, José Ángel; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick; Delgado, Anabel D.; Flores de los Ríos, Juan Pablo; Bocchetta, Patrizia; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2022)
Titanium and its alloys have superior electrochemical properties compared to other alloy systems due to the formation of a protective TiO2 film on metal surfaces. The ability to generate the protective oxide layer will depend upon the type of alloy to be used. The aim of this work was to characterize the electrochemical corrosion behavior of titanium Ti-CP2 and alloys Ti-6Al-2Sn-4Zr-2Mo, Ti-6Al-4V, and Ti Beta-C. Samples were anodized in 1 M H2SO4 and H3PO4 solutions with a current density of 0.025 A/cm2. Electrochemical tests on anodized alloys were carried out using a three-electrode cell and exposed in two electrolytes, i.e., 3.5 wt % NaCl and 3.5 wt % H2SO4 solutions at room temperature. Scanning electron microscopy (SEM) was used to observe the morphology of anodized surfaces. The electrochemical techniques used were cyclic potentiodynamic polarization (CPP) and electrochemical noise (EN), based on the ASTM-G61 and G199 standards. Regarding EN, two methods of data analysis were used: the frequency domain (power spectral density, PSD) and time-frequency domain (discrete wavelet transform). For non-anodized alloys, the results by CCP and EN indicate icorr values of ×10−6 A/cm2. However, under anodizing conditions, the icorr values vary from ×10−7 to ×10−9 A/cm2. The PSD Ψ0 values are higher for non-anodized alloys, while in anodized conditions, the values range from −138/−122 dBi (A2·Hz−1)1/2 to −131/−180 dBi (A2·Hz−1)1/2. Furthermore, the results indicated that the alloys anodized in the H3PO4 bath showed an electrochemical behavior that can be associated with a more homogeneous passive layer when exposed to the 3.5 wt % NaCl electrolyte. Alloys containing more beta-phase stabilizers formed a less homogeneous anodized layer. These alloys are widely used in aeronautical applications; thus, it is essential that these alloys have excellent corrosion performance in chloride and acid rain environments